Effectiveness and Safety of Inhaled Antibiotics in Patients With Chronic Obstructive Pulmonary Disease. A Multicentre Observational Study - De la Rosa Carrillo, David; Martínez-García, Miguel Ángel; Barreiro, Esther; Tabernero Huguet, Eva; Costa Sola, Roser; García-Clemente, Marta María; Celorrio Jiménez, Nuria; Rodríguez Pons, Laura; Calero Acuña, Carmen; Rodríguez Hermosa, Juan Luís; Golpe, Rafael; Dacal Quintas, Raquel; et al. (Archivos de bronconeumología (English ed.), 2022)
We aimed to describe the effectiveness and safety of inhaled antibiotics in chronic obstructive pulmonary disease (COPD) patients, as well as the patient profile in which they are usually prescribed and the patient groups that can most benefit from this treatment. Multicentre retrospective observational cohort study in COPD patients who had received ≥1 dose of inhaled antibiotics in the last 5 years. Clinical data from the two years prior to and subsequent to the start of the treatment were compared. COPD exacerbations. side effects, symptomatology (sputum purulence, dyspnoea), microbiological profile and pathogen eradication. Of 693 COPD patients analyzed (aged 74.1; 86.3% men; mean FEV =43.7%), 71.7% had bronchiectasis and 46.6% presented chronic bronchial infection (CBI) by Pseudomonas aeruginosa (PA). After 1 year of treatment with inhaled antibiotics, there was a significant decrease in the number of exacerbations (-33.3%; P<.001), hospital admissions (-33.3%; P<.001) and hospitalization days (-26.2%; P=.003). We found no difference in effectiveness between patients with or without associated bronchiectasis. Positive patient outcomes were more pronounced in PA-eradicated patients. We found a significant reduction in daily expectoration (-33.1%; P=.024), mucopurulent/purulent sputum (-53.9%; P<.001), isolation of any potentially pathogenic microorganisms (PPM) (-16.7%; P<.001), CBI by any PPM (-37.4%; P<.001) and CBI by PA (-49.8%; P<.001). CBI by any PPM and ≥three previous exacerbations were associated with a better treatment response. 25.4% of patients presented non-severe side-effects, the most frequent of these being bronchospasm (10.5%), dyspnoea (8.8%) and cough (1.7%). In COPD patients with multiple exacerbations and/or CBI by any PPM (especially PA), inhaled antibiotics appear to be an effective and safe treatment, regardless of the presence of bronchiectasis.